2017
DOI: 10.1016/j.pedn.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Parental expectations of support from healthcare providers during pediatric life-threatening illness: A secondary, qualitative analysis

Abstract: Purposes To explain parental expectations of support from healthcare providers for their parenting roles and goals during a child’s life-threatening illness (LTI). Design and Methods Qualitative interpretive study guided by the Family Adjustment and Adaptation Response Model. Thematic analyses were conducted with data from 31 semi-structured interviews of parents of children with LTI using systematic strategies to ensure rigor including audit trails and prolonged engagement. Results We identified three the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 60 publications
1
22
0
1
Order By: Relevance
“…Paediatric Palliative Care (PPC) is defined as an active, total approach to the holistic care of the child and family (WHO, 1998). Close, long lasting, relationships between healthcare professionals and parents in PPC are an important source of emotional support and can influence the way in which parents manage uncertainty (Rodriguez and King, 2014, Mooney-Doyle et al, 2017. Whilst these relationships can enhance quality (Klassen, 2012, Buder andFringer, 2016) and job satisfaction, they often carry an emotional burden; hence managing them is a challenge (Rushton and Ballard, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Paediatric Palliative Care (PPC) is defined as an active, total approach to the holistic care of the child and family (WHO, 1998). Close, long lasting, relationships between healthcare professionals and parents in PPC are an important source of emotional support and can influence the way in which parents manage uncertainty (Rodriguez and King, 2014, Mooney-Doyle et al, 2017. Whilst these relationships can enhance quality (Klassen, 2012, Buder andFringer, 2016) and job satisfaction, they often carry an emotional burden; hence managing them is a challenge (Rushton and Ballard, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by Weaver et al [ 46 ] and Moonley et al, [ 47 ] who strengthen the role of relationships between parents and health care professionals in order to help families to cope with the uncertainty and adversity of their child’s illness, leading to mixed, sometimes dichotomous feelings such as joy and sadness, hope and despair as reported by Rallison [ 48 ].…”
Section: Discussionmentioning
confidence: 83%
“…In this study, we identified our partial knowledge about family, children during the dying process, and palliative care developed in previous research (Santos et al, 2019a; Mooney-Doyle et al, 2017; Wiegand et al, 2015; Misko et al, 2015). These pre-judgments have not only motivated us to focus on the relationship between families and care providers but are inevitably preconceptions which are modified as new questions arose during the research process in the research team.…”
Section: Methodsmentioning
confidence: 99%